Prevalence and factors associated to diffuse idiopathic skeletal hyperostosis in gout - Fernando Pérez-Ruiz; Nuria Perez-Herrero; Cristina Vazquez-Puente; Maria del Consuelo Modesto-Caballero; Nerea Perez-Herrero; Ana María Herrero-Beites (Exploration of Musculoskeletal Diseases, 2023)
Aim: To evaluate the prevalence, associated factors, and the impact of diffuse idiopathic skeletal hyperostosis (DISH) in patients with gout. Methods: Patients with gout entering into an inception cohort were evaluated for either spinal or peripheral hyperostosis from January 2022 to April 2023. Age, gender, along with comorbid conditions associated to gout and DISH were analyzed, including the presence either axial or peripheral hyperostosis and associated calcium pyrophosphate arthritis (CPPA). Results: The prevalence of DISH was 25.6% (31/121) patients, neat peripheral joint hyperostosis affecting 51.6% (16/31). CPPA was also present in 11.6% (14/121) patients. Only older age and male gender were independently associated to the presence of DISH. The presence of hyperostosis in peripheral joints was not associated to a worse initial evaluation of the severity of gout. Conclusions: The presence of DISH in patients with gout seems to be related mostly to aging. Conditions apparently associated to DISH in gout patients seem therefore to be related to aging.